2023
DOI: 10.1038/s41586-023-06054-z
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer whole-genome comparison of primary and metastatic solid tumours

Abstract: Metastatic cancer remains an almost inevitably lethal disease1–3. A better understanding of disease progression and response to therapies therefore remains of utmost importance. Here we characterize the genomic differences between early-stage untreated primary tumours and late-stage treated metastatic tumours using a harmonized pan-cancer analysis (or reanalysis) of two unpaired primary4 and metastatic5 cohorts of 7,108 whole-genome-sequenced tumours. Metastatic tumours in general have a lower intratumour hete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(33 citation statements)
references
References 61 publications
1
32
0
Order By: Relevance
“…al. found that the metastatic tumors have a higher frequency of structural variants 8 . Incorporating additional structural mutation signature data and copy number variations (CNVs) has the potential to further improve AI algorithms from diverse multi-omics datasets.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…al. found that the metastatic tumors have a higher frequency of structural variants 8 . Incorporating additional structural mutation signature data and copy number variations (CNVs) has the potential to further improve AI algorithms from diverse multi-omics datasets.…”
Section: Discussionmentioning
confidence: 94%
“…The mutational signature contribution matrices pertaining to primary breast cancers within the Pan-Cancer Analysis of Whole Genomes (PCAWG) cohort, and metastatic breast cancers within the Hartwig Medical Foundation (HMF) cohort, were extracted from the supplementary tables of the reference 8 . The dataset encompasses two types of contribution matrices.…”
Section: Genomic Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copy number data of primary tumors of various entities and their respective metastases unveiled highly increased ratios of chr8p loss in the metastatic tissue compared to the corresponding primary site (fig. S3A) ( 27 , 28 ). Moreover, chr8p deletion was more prominent in distant than in local metastasis sites indicating chr8p loss to be a beneficial factor for the metastatic capacity of cancer cells (fig.…”
Section: Resultsmentioning
confidence: 99%
“…The rate of SBS1 accumulation varies among cell types and increases with the rate of cellular turnover [3,18]. The loading of SBS1 mutations has also been found to increase in metastatic tumours relative to their primary tumour counterparts, plausibly due to accelerated cell division rates in metastasis [19]. In contrast, SBS5 has a more diffuse distribution among the 96 SBS types.…”
Section: Introductionmentioning
confidence: 99%